1984
DOI: 10.1161/01.atv.4.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Neutral triglyceride lipase in macrophages.

Abstract: High levels of neutral triglyceride lipase activity have been demonstrated In several types of macrophages (J774 cells, human monocyte/macrophages, rabbit alveolar macrophages, and resident mouse peritoneal macrophages). The pH optima ranged from 6.5 to 7.4 depending upon the buffer and the conditions of incubation. The addition of bovine serum albumin stimulated activity at low concentrations, as expected for a fatty acid-releasing reaction, but strongly inhibited at higher concentrations; maximal activity wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…Recent studies from this laboratory have demonstrated the presence in several types of macrophages of a very high level of neutral lipase activity that may be responsible for the observed rapid mobilization of stored glycerides. 20 The pattern is reminiscent of that in adipose tissue, the only tissue in which net release of FAA is a prominent pathway. 21 Ehrlich ascites tumor cells in culture can release FFA in net fashion when albumin containing no FFA is present in the medium, but net release in vivo is unlikely.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies from this laboratory have demonstrated the presence in several types of macrophages of a very high level of neutral lipase activity that may be responsible for the observed rapid mobilization of stored glycerides. 20 The pattern is reminiscent of that in adipose tissue, the only tissue in which net release of FAA is a prominent pathway. 21 Ehrlich ascites tumor cells in culture can release FFA in net fashion when albumin containing no FFA is present in the medium, but net release in vivo is unlikely.…”
Section: Discussionmentioning
confidence: 96%
“…Earlier studies [22,23], related to oil-water interface reaction of porcine pancreatic lipase have shown that the presence of low concentration of BSA is able to protect lipase from denaturation. However, at higher concentrations of BSA (2.75 mg/ml [24]) the reduction of lipase activity was observed and attributed to decreased lipase binding at the interface [22][23][24][25][26].…”
Section: Effect Of Bovine Serum Albuminmentioning
confidence: 99%
“…Neutral triglyceride lipase was assayed in postnuclear homogenates according to the methods described by Khoo et al 25 Substrate was prepared by drying down 15 mg triolein and 6.4 jtCi glycerol tri-9,10(n)-3 l+oleate under N 2 , dissolving it in 1 ml 100% ethanol, rapidly injecting it into 16 ml distilled water, and vortexing vigorously for 1 minute, followed by the addition of 8 ml of HEPES buffer (0.2 M, pH 6.6) and further vortexing. The cells were harvested and homogenized as described above.…”
Section: Assay Of Neutral Triglyceride Upase Activitymentioning
confidence: 99%
“…2223 Finally, the lipids stored within the cell are continuously hydrolyzed by the action of cytoplasmic lipases. 24 - 25 Since macrophages are immunocompetent cells that can exist in vivo within a spectrum of functional states of activation, which range from unstjmulated or resident cells that display low levels of metabolic and phagocytic activities to fully activated cells that display new biochemical features, 2627 it would not be surprising for activation to be associated with changes in lipid homeostatic pathways. Indeed, a number of alterations have been observed to occur in macrophage lipid and lipoprotein metabolism with activation.…”
mentioning
confidence: 99%